(untitled) (Journal of Advanced Veterinary and Animal Research, 2017)
Objectives: The objective of this study was to identify the current status of emerging diseases of pet animals in Bangladesh and to estimate the percentage of disease occurrence in the pet animals. Materials and methods: A 2-month potential study was conducted to estimate the percentage (%) of disease occurrence and current status of emerging diseases of pet animals in Bangladesh. A total of 550 animals were examined and 358 data were collected from the disease registered book of the Central Veterinary Hospital (CVH), Dhaka and SA Quaderi Teaching Veterinary Hospital, Chittagong Veterinary and Animal Sciences University (CVASU), Bangladesh during June and September, 2014. The data were analysed, and the results on the newly emerging diseases were expressed as percentage (%). Results: Among the most general pet animals in Bangladesh (dog, cat, rabbit), the mostly occured diseases were scabies (23.07%), feline ascariasis (37.14%) and rabbit mange (34.61%), while the less frequent diseases were canine parvovirus enteritis (2.19%), cat scratch disease (5.71%) and overgrown teeth (7.69%). Conclusion: The study provides basic information about the current status and the percentage (%) of disease occurrence considering the emerging diseases of pet animals in Bangladesh. http://doi.org/10.5455/javar.2016.c182